2000
DOI: 10.1097/00004872-200018110-00006
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training normalizes wall-to-lumen ratio of the gracilis muscle arterioles and reduces pressure in spontaneously hypertensive rats

Abstract: The results suggest that low-intensity training can significantly reduce pressure in SHR while normalizing both the arteriole morphology and the resistance of the skeletal muscle microcirculation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
121
7
60

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(205 citation statements)
references
References 33 publications
17
121
7
60
Order By: Relevance
“…Indeed, Moreno et al (27) reported a high kidney weight in female hypertensive rats (vs normotensive controls), which could be a useful "intermediate phenotype" of hypertension. These observations agree with pressure measurements obtained by us and by others: male SHR had higher pressure levels than female SHR (range of 170-185 vs 150-160 mmHg for males and females, respectively) (22,25,26). In general, sex differences have not been extensively explored, since most of the studies were done with male animals.…”
Section: Mechanisms Conditioning Cardiovascular Changes In Hypertensionsupporting
confidence: 91%
See 4 more Smart Citations
“…Indeed, Moreno et al (27) reported a high kidney weight in female hypertensive rats (vs normotensive controls), which could be a useful "intermediate phenotype" of hypertension. These observations agree with pressure measurements obtained by us and by others: male SHR had higher pressure levels than female SHR (range of 170-185 vs 150-160 mmHg for males and females, respectively) (22,25,26). In general, sex differences have not been extensively explored, since most of the studies were done with male animals.…”
Section: Mechanisms Conditioning Cardiovascular Changes In Hypertensionsupporting
confidence: 91%
“…In spontaneously hypertensive rats (SHR), the best known experimental model for essential or primary hypertension in humans, we confirmed that high blood pressure levels are accompanied by remodeling of arterioles (increased wall-to-lumen ratio) and capillary rarefaction in many tissues including the skeletal muscles, in which we demonstrated a normal resting blood flow, besides the altered vascular structure (22)(23)(24)(25)(26). According to Mulvany (16), vascular remodeling in hypertension is characterized by increased wall-to-lumen ratio of arteries and arterioles, being classified as eutrophic (decrease in both lumen and outer diameter, with unaltered wall thickness or cross-sectional area) or hypertrophic (increase in media thickening, that encroaches on the lumen).…”
Section: Mechanisms Conditioning Cardiovascular Changes In Hypertensionsupporting
confidence: 67%
See 3 more Smart Citations